Construction of well aligned highly dense Cobalt nanoneedles for efficient device application. Issue 4 (2nd October 2017) - Mishra, Suryakant; Yogi, Priyanka; Saxena, Shailendra; Roy, Swarup; Sagdeo, P. R.; Kumar, Rajesh
Abstract: One step morphology transformation has been reported here by the addition of ammonium fluoride. Two different morphologies of the same structure have been reported for Cobalt Oxide nanostructures. Cobalt oxide nanoneedles in which, one is sleazy needles (s-NDs) and other one is erected needles (e-NDs) have been synthesised. Hydrothermal method has been used for the construction of both the nanoneedles structure. Morphological study by SEM attributes conversion of sleazy bowed done shape to well aligned ones, highly dense and sharp nanostructures. Quantitative analysis shows that after addition of ammonium fluoride, randomly distributed network of nanoneedles converts into a surface covered with vertically aligned, sharp and dense nanoneedles.